Pandemi Covid-19 dan Dampaknya Terhadap Perubahan Kebijakan Perusahaan Sektor Teknologi - Wiwik Andriani; Rangga Putra Ananto; Eka Rosalina; Wina Nofrima Fitri; Dandi Aprila (Pusat P2M Politeknik Negeri Batam, 2022)
Analysis conducted to see the extent to which a company has implemented by using financial implementation rules correctly and adequately is called financial performance. There are 5 (five) ratios used in assessing the company's financial performance, including liquidity ratios, leverage ratios, activity ratios, profitability ratios, and market value ratios. This study aims to determine a policy strategy based on the results of a comparison test of the financial performance of technology sector companies before and during the 2018-2021 period of the covid-19 pandemic. In this study, secondary data are used. Purposive sampling was utilized as the sampling methodology. This study employed a normality test and Paired Sample T-Test. The results of this study indicate that the financial performance of technology companies during the covid-19 pandemic got significant results for all variables. Based on the comparison test results, a policy strategy is needed to solve the problems related to financial performance.